Assessment and Metacognition in the classroom - Delgado Santa Gadea, Kenneth (2014)
Metacognition is an opportunity for self-assessment and for the inter-assessment in the classroom. This is a necessary practice for the development of a formative evaluation; this process will not be restricted to summative evaluation. Through the learning socialization, teachers can develop metacognition in the classroom so that students can learn to learn by themselves; they will also perceive their knowledge and what it is that they still need to learn. Thus, the motivation for learning will increase.